Exploring The Role Of Sharia Fintech In Supporting The Islamic Economy In The Era Of Financial Digitalization - Alifa Rahma Oktantia; Hendri Hermawan Adinugraha (Yayasan Abdurrauf Cendekia Nusantara, 2025)
Financial digitalization has brought significant changes to the modern economic system through the emergence of various financial technology innovations. In countries with predominantly Muslim populations, sharia fintech has emerged as a digital financial solution that integrates Islamic principles with technological advancement. This study aims to explore the role of sharia fintech in supporting economic growth in the era of financial digitalization and to identify its contributions, opportunities, and challenges. This research employs a qualitative approach through a literature review and descriptive analysis of academic journals, industry reports, and regulations related to sharia fintech and the digital economy. The analytical framework is based on financial inclusion, technological innovation, and maqashid sharia as the foundation of Islamic financial development. The findings indicate that sharia fintech plays a crucial role in enhancing financial inclusion, particularly for underserved communities, and in expanding access to financing for micro, small, and medium enterprises through sharia-compliant digital platforms. Moreover, sharia fintech supports economic stability and growth by offering a more transparent, ethical, and equitable financial system. However, the development of sharia fintech still faces several challenges, including low levels of digital sharia financial literacy, infrastructure limitations, and the need for more adaptive regulations and stronger sharia supervision. Therefore, collaboration among governments, regulators, and industry stakeholders is essential to ensure that sharia fintech can optimally contribute to sustainable economic development in the digital era.